2023
DOI: 10.3390/cells12071088
|View full text |Cite
|
Sign up to set email alerts
|

High Mobility Group Box 1 (HMGB1): Potential Target in Sepsis-Associated Encephalopathy

Abstract: Sepsis-associated encephalopathy (SAE) remains a challenge for intensivists that is exacerbated by lack of an effective diagnostic tool and an unambiguous definition to properly identify SAE patients. Risk factors for SAE development include age, genetic factors as well as pre-existing neuropsychiatric conditions. Sepsis due to certain infection sites/origins might be more prone to encephalopathy development than other cases. Currently, ICU management of SAE is mainly based on non-pharmacological support. Pre-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 158 publications
0
3
0
Order By: Relevance
“…Eliminating the inflammatory cascade by HMGB1 may be a strategy to complement nonpharmacological interventions targeting SAE 37 . Inflachromene inhibits the expression of HMGB1 and IBA-1 in the hippocampus of CLP mice and restores cognitive function 6 .…”
Section: Discussionmentioning
confidence: 99%
“…Eliminating the inflammatory cascade by HMGB1 may be a strategy to complement nonpharmacological interventions targeting SAE 37 . Inflachromene inhibits the expression of HMGB1 and IBA-1 in the hippocampus of CLP mice and restores cognitive function 6 .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in vivo experiments demonstrated that salidroside treatment decreases NET production via the HMGB1/TLR4/MAPK signaling pathway, thereby improving hepatic dysfunction, decreasing inflammatory cytokines, and attenuating hepatic histopathological changes. HMGB1, which is a protein that is found in large quantities in chromosomes, acts as a damage-associated molecular pattern that initiates innate inflammatory responses against infection and injury [32]. HMGB1 contributes to the pathogenesis of multiple liver diseases, such as hepatic IRI and acute liver rejection, through TLRs [33].…”
Section: Discussionmentioning
confidence: 99%
“…HMGB1, which is a protein that is found in large quantities in chromosomes, acts as a damage-associated molecular pattern that initiates innate inflammatory responses against infection and injury [32] . HMGB1 contributes to the pathogenesis of multiple liver diseases, such as hepatic IRI and acute liver rejection, through TLRs [33] .…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice, the presence of sepsisassociated delirium is often utilized as a substitute for diagnosing SAE (6), and delirium is evaluated by using a subjective scoring method known as CAM-ICU. Despite the existence of some biomarkers like neurofilament light chains (NFL), S100 calciumbinding protein B (S100β), and neuron-specific enolase (NSE) for predicting the occurrence of SAE (7)(8)(9), these biomarkers are not readily accessible in clinical settings and lack the necessary sensitivity and specificity for accurately predicting SAE. Consequently, new predictive indicators, including clinical parameters, are required to aid in prediction.…”
Section: Introductionmentioning
confidence: 99%